Biosafety Regulation: a comparative analysis of the South African and Ugandan experience - Joy, Faida (Institute of Marine and Environmental Law, 2014)
This study provides a critical and comparative analysis of biosafety regulation in South Africa and Uganda. The overall objective of the study is to establish which country prescribes a more adequate regulatory regime. Biosafety regulation under international and regional law is the first key aspect that this paper examines. This is done in order to set out a context under which domestic biosafety regulation is examined. This study argues that international law generally sets minimum standards while regional law sets higher standards for biosafety regulation. The second key area examined is biosafety regulation in South Africa. The paper sets out an overview of the relevant biosafety laws in South Africa and conducts a critical analysis of these laws pointing out their strengths and weaknesses. The study is premised on the argument that South African regulatory regime is inadequate for purposes of regulating biosafety. The third part of this paper focuses on Uganda's regulatory regime. A similar analysis was carried where the study found that the Ugandan regime is reasonably adequate for purposes of protection of the environment and human health. The final key aspect of this paper is a comparative analysis of biosafety regulation in South Africa and Uganda. This is done thematically, setting out differences and similarities. This part examines the extent to which South Africa and Uganda have attempted to comply with their international obligations. This paper concludes that, although the Ugandan regulatory regime (both existing and proposed) has some weaknesses, it is a more adequate regime than the South African one. Further, Uganda is more compliant with the biosafety Protocol and the African Model Law than South Africa.